2010
DOI: 10.3174/ajnr.a2272
|View full text |Cite
|
Sign up to set email alerts
|

Stent-Assisted Coiling of Complex Middle Cerebral Artery Aneurysms: Initial and Midterm Results

Abstract: BACKGROUND AND PURPOSE:Clinical outcome and initial and midterm angiographic results of EVT of complex MCA aneurysms by using the stent-assisted coiling technique were retrospectively evaluated in our center where EVT of intracranial aneurysms is the first treatment option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 34 publications
4
49
0
1
Order By: Relevance
“…34 Several series have recently been published that focus specifically on complex MCA aneurysms. 26,27,35 In the largest series, Johnson et al 26 treated 100…”
Section: Adjunctive Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Several series have recently been published that focus specifically on complex MCA aneurysms. 26,27,35 In the largest series, Johnson et al 26 treated 100…”
Section: Adjunctive Therapiesmentioning
confidence: 99%
“…This trend may explain the relatively low thromboembolic complication rate, but also lower rates of complete occlusion compared with some recently published series on use of adjunctive devices. 26,27 Adjunctive devices have been used in 20.4% of other published MCA series, 22 with the aim of obtaining complete occlusion to minimize the risk for subsequent hemorrhage. 28 A critical appraisal of the available literature has suggested that balloon assistance has a very similar safety profile to coiling without remodeling.…”
Section: Adjunctive Therapiesmentioning
confidence: 99%
“…In endovascular embolization, difficulties may be created by the size of the aneurysm and its neck rather than its location 17 . The introduction of the stent-assisted technique 18 and the development of various soft coils have significantly improved the anatomical results of coil embolization in this kind of aneurysm by permitting tight coil packing and a more complete occlusion of the lesion's inflow. Therefore, an alternative endovascular technique would be of particular benefit in this group of patients.…”
Section: Endovascular Treatment For Multiple Intracranial Aneurysmsmentioning
confidence: 99%
“…Bifurcation aneurysms are a challenging entity to treat and a wide variety of different coiling methods, including balloon-assisted, stent-assisted and the waffle cone technique have been used to treat these aneurysms [1][2][3][4][5][6][7]. Dedicated devices have recently entered the market that have been designed specifically to assist in the treatment of these aneurysms and include the pCONus1 and pCONus2 (phenox, Bochum, Germany), the PulseRider ® (Pulsar Vascular, Los Gatos, CA, USA), and the eCLIPs™ device (Evasc Neurovascular Enterprises, Vancouver, BC, Canada).…”
Section: Introductionmentioning
confidence: 99%